2022
DOI: 10.48550/arxiv.2203.15661
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Temporal Robustness of Temporal Logic Specifications: Analysis and Control Design

Alëna Rodionova,
Lars Lindemann,
Manfred Morari
et al.

Abstract: We study the temporal robustness of temporal logic specifications and show how to design temporally robust control laws for time-critical control systems. This topic is of particular interest in connected systems and interleaving processes such as multi-robot and human-robot systems where uncertainty in the behavior of individual agents and humans can induce timing uncertainty. Despite the importance of time-critical systems, temporal robustness of temporal logic specifications has not been studied, especially… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 43 publications
(116 reference statements)
0
4
0
Order By: Relevance
“…Formally, if θ ± ϕ (x,t) > 0 then χ ϕ (x,t) = 1 and if θ ± ϕ (x,t) < 0 then χ ϕ (x,t) = −1. In [15], we also showed that the absolute value of the left (right) time robustness measures how robustly a signal x satisfies a formula ϕ at time t with respect to time shifts in the predicates of formula ϕ. In fact, one can asynchronously shift predicates in time to the left by up to |θ + ϕ (x,t)| and the specification will not change its satisfaction.…”
Section: Signal Temporal Logic (Stl)mentioning
confidence: 91%
See 3 more Smart Citations
“…Formally, if θ ± ϕ (x,t) > 0 then χ ϕ (x,t) = 1 and if θ ± ϕ (x,t) < 0 then χ ϕ (x,t) = −1. In [15], we also showed that the absolute value of the left (right) time robustness measures how robustly a signal x satisfies a formula ϕ at time t with respect to time shifts in the predicates of formula ϕ. In fact, one can asynchronously shift predicates in time to the left by up to |θ + ϕ (x,t)| and the specification will not change its satisfaction.…”
Section: Signal Temporal Logic (Stl)mentioning
confidence: 91%
“…and then, to obtain the θ ± ϕ (x,t), one needs to apply the standard recursive inf/sup rules to each θ ± p (x,t), similarly to the characteristic function χ ϕ (x,t), see [15] for details.…”
Section: Signal Temporal Logic (Stl)mentioning
confidence: 99%
See 2 more Smart Citations